Fabrication and characterization of electrospun κ-carrageenan based oral dispersible ﬁlm with vitamin C - Nurul Haiza, Sapiee; Muhammad Hasif, Mat Saufi; Noor Fitrah, Abu Bakar; Fatmawati, Adam (Elsevier Ltd, 2023)
Oral dispersible films (ODF) are great alternatives to tablet medications as they will simply dissolve in the mouth. There are several ways to produce ODFs, but electrospinning is emerging as one of the best methods as it increases the surface to volume ratio which allows it to dissolve easily. ODFs are typically formulated using a combination of polymers to produce the necessary film qualities. The use of κ-carrageenan (κ-CAR), a natural polymer in ODFs are yet to be studied in detail. Therefore, this study aims to develop an ODF from a combination of κ-CAR, polyvinyl alcohol (PVA) and vitamin C, where the latter will act as a model drug carrier. 1.5w/v% κ-CAR and 14w/v% PVA at a ratio of 30:70 was added with different concentrations of vitamin C from 2 to 10w/v%, respectively. The resulting nanofibers were then examined for morphology, water contact angle (WCA) and disintegration time. All the solutions formed uniform nanofibers with an average diameter ranging from 190 to 490 nm and showed hydrophilic properties. Sample 4 showed the fastest disintegration time of 3.68 s and the lowest WCA of 38.5°. The results indicated that the best formulation for an ODF was with 8% vitamin C. The findings from this study provide promising groundwork for the use of κ-CAR as the biopolymer in combination with the PVA to develop a biopolymer-based ODF with vitamin C via electrospinning.